Determinan Profitabilitas PT. BPR BANK BAPAS 69 - Muhammad Danil Shani; Heni Hirawati (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This research aims to determine and analyze profitability at PT. BPR BANK BAPAS 69. The method used in this research is multiple linear regression analysis with Stata 16.0. The data used is secondary data from the website PT. BPR BANK BAPAS 69 during 2016-2020 period. Based on the research results, it is known that CAR, NPL, and LDR as independent variables have a significant effect on ROA as the dependent variable with a significance value of 0.0447. Based on the results of hypothesis testing, found that the CAR and LDR variables have a negative and insignificant effect on ROA. The NPL variable has a negative and significant effect on ROA. Of the three independent variables, NPL has the biggest effect on ROA with a coefficient value of -2.892877.